EFEKTIVITAS BAWANG PUTIH DENGAN METODE MARINASI TERHADAP KUALITAS FISIK DAGING BROILER - Pratama, Ridho; Riyanti, Rr; Husni, Ali (JURUSAN PETERNAKAN, FAKULTAS PERTANIAN, UNIVERSITAS LAMPUNG, 2018)
This research aims to know the efectivity of garlic by marination method on physical quality of broiler meat such as pH, water holding capacity, and cooking loss. Research was conducted on 8 Mei 2017 in Laboratory Animal Production and Reproduction, Animal Husbandry, Lampung University. The material used in this experiment was broiler meat from chicken slaughterhouse and chinese garlic blend. This research has done based Completely Randomized Design (CRD) with 4 treatments and 5 replications. The treatments is marinating with a blend of garlic 4% (T1), 8% (T2), 12% (T3), and non marinated (T0). Obtained data were analyzed with the assumptions of variance by 5% or 1%, then the result were significantly different in the advanced test using Least Significant Different (LSD). Results showed that marinating blend of garlic significantly affected (P<0,01) to water holding capacity and cooking loss, but did not significantly affect (P>0,05) to pH. Marinated broiler meat with garlic blend at a concentration of 12% yields the best water holding capacity and cooking loss. Keywords: garlic, broiler meat, marination, pH, water holding capacity, cooking loss.